Turning Pro : Raising the Level of Professionalism in Ukraine's Leasing Industry - Mehrengs, Ernst; Ockman, Sarah (World Bank, Washington, DC, 2012)
In 2005, leasing companies in Ukraine were continually telling us that their main impediment to growth was the lack of professional staff. The leasing market in the country was growing at a tremendous rate: the overall leasing portfolio had more than doubled from year to year, reaching almost $350 million by the end of 2005, and the number of jobs in the leasing market was experiencing similar growth. It was therefore increasingly difficult to find qualified professionals who had experience in leasing. Raising the level of professionalism and status of leasing specialists seemed to be the answer to this problem, and local certification was one way to do it. While the program seemed a daunting and overwhelming task at first, it proved more manageable once initial management skepticism was overcome, the structure of the program was designed, and the partners were involved. The certification program is now in its second year, has trained over 150 people, and has gained a good reputation. It is also a good source for leasing companies to recruit and retain professional staff. 'In the short term, this certification program helps to improve the skills of our own employees, but more importantly, it is useful for building a critical mass of professionals in the leasing industry, and it will create a foundation for sustainable growth in the leasing business in Ukraine'.